Konsep Pembelajaran Matematika Sekolah Dasar Berlandaskan Teori Kognitif Jean Piaget - Indri Fitriani Juardi; Komariah Komariah (Departement of Mathematics Education, 2023)
This study aims to explain the concept of learning mathematics in elementary schools based on Jean Piaget's cognitive theory. The focus of this research is how the concept of learning mathematics at the elementary school level is based on Jean Piaget's cognitive theory. This study used a qualitative approach with a library survey data collection method. The data analysis carried out in this study is a form of data analysis using the Miles and Huberman model with three stages of data analysis. From the results of this study it was found that elementary school students are children aged 7 to 12 years who are in the concrete action stage, and they understand reversible and conservative logic operations in the concrete action stage.